Ecophysiological traits differentially modulate secondary metabolite accumulation and antioxidant properties of tea plant [Camellia sinensis (L.) O. Kuntze] - Anjan Hazra (Nature Portfolio, 2021)
Abstract Owing to the diverse growing habitats, ecophysiology might have a regulatory impact on characteristic chemical components of tea plant. This study aimed to explore natural variations in the ecophysiological traits within seasons and the corresponding multifaceted biochemical responses given by the gene pool of 22 tea cultivars. Leaf temperature and intercellular carbon concentration (Ci), which varies as a function of transpiration and net photosynthesis respectively, have significant impact on the biochemical traits of the leaf. Occurrence of H2O2, in leaves, was associated to Ci that in turn influenced the lipid peroxidation. With the increment of Ci, total phenolics, epicatechin gallate (ECG), reducing power, and radical scavenging activity is lowered but total catechin and non-gallylated catechin derivatives (e.g. epicatechin or EC, epigallocatechin or EGC) are elevated. Leaf temperature is concomitantly associated (p ≤ 0.01) with phenolics, flavonoids, proanthocyanidin, tannin content, reducing power, iron chelation and free radical scavenging activities. Increased phenolic concentration in leaf cells, conceivably inhibit photosynthesis and moreover, gallic acid, thereafter conjugated to catechin derivatives. This study shed light on the fundamental information regarding ecophysiological impact on the quality determining biochemical characteristics of tea, which on further validation, might ascertain the genotype selection paradigm toward climate smart cultivation.